AN ANALYSIS OF THE STUDENTS’ WRITING ERROR IN REPORT TEXT - PRAYUDA, MEIKARDO SAMUEL (Jurnal Ilmiah Aquinas, 2020)
This research purposed to measure the students’writing errors in report text so that it can find the kinds of errors that faced by the students in the writing of report text. The subject of this research were the students of grade X at SMA Negeri 1 Sei. Balai in academic year of 2015/2016. The population of the research were 105 students in three classes while the sample were 27 students. This research was conducted in descriptive research and the method in taking the sample was random sampling. The instruments for this researchwere observation and interview. The result of this study was that most students did errors in the word form. 11 students did errors in their construction in word form in writing report text and then followed by the errors in word choice. 10 students did errors in their word choice. Next, followed by error in punctuation. 9 students did error in the punctuation. It is suggested in teaching writing especially in writing report text, the teacher should put a serious intention in the part of word choice, word form, and also punctuation since these instruments are the most troublesome parts in this study of the students’ writing error